Răspuns :
a+b+c=192 +
b-c=123
__________
a+2b =192+123
a+2b= 315
2a+b+3c= 2a +4b- 3b+3c= 2*(a+2b)-3*(b-c)= 2*315 - 3*123=630-369= 261
b-c=123
__________
a+2b =192+123
a+2b= 315
2a+b+3c= 2a +4b- 3b+3c= 2*(a+2b)-3*(b-c)= 2*315 - 3*123=630-369= 261
a+b+c=192
b-c=123
se aduna ambele ecuatii
a+b+c+b-c=192+123
a+2b= 315
2a+b+3c= se desface in : 2a +4b- 3b+3c=
(a+2b)+(a+2b)-3×(b-c)= 315+315 -3×123=630-369= 261
2a+b+3c=261
b-c=123
se aduna ambele ecuatii
a+b+c+b-c=192+123
a+2b= 315
2a+b+3c= se desface in : 2a +4b- 3b+3c=
(a+2b)+(a+2b)-3×(b-c)= 315+315 -3×123=630-369= 261
2a+b+3c=261